Implementation Of Ethnomathematics Using the Trello Application to Increase Students’ Numeracy and Digital Literacy - Kusuma, Dianne Amor; Delima, Nita; Widodo, Sri Adi; Dwipriyoko, Estiyan (Universitas Sarjanawiyata Tamansiswa, 2024)
This research is motivated by technological advances that are developing more rapidly so that it can be used to improve students’ numeracy and digital literacy. This research aimed to analyse the impact of applying Ethnomathematics using the Trello application in increasing university students' numeracy literacy and digital literacy. This research used a survey method on 56 students. The research instruments used were a numeracy literacy test in the mathematics-chemistry one course, a digital literacy questionnaire, and an interview sheet. This research shows that implementing ethnomathematics utilising the application of Trello has several advantages, including increasing university students' numeracy and digital literacy.